Occupational exposure to endocrine disruptors and lymphoma risk in a multi-centric European study - Costas, L; Infante-Rivard, C; Zock, J-P; Van Tongeren, M; Boffetta, P; Cusson, A; Robles, C; Casabonne, D; Benavente, Y; Becker, N; Brennan, P; Foretova, L; et al. (British journal of cancer, 2015)
BACKGROUND: Incidence rates of lymphoma are usually higher in men than in women, and oestrogens may protect against lymphoma. METHODS: We evaluated occupational exposure to endocrine disrupting chemicals (EDCs) among 2457 controls and 2178 incident lymphoma cases and subtypes from the European Epilymph study. RESULTS: Over 30 years of exposure to EDCs compared to no exposure was associated with a 24% increased risk of mature B-cell neoplasms (P-trend=0.02). Associations were observed among men, but not women. CONCLUSIONS: Prolonged occupational exposure to endocrine disruptors seems to be moderately associated with some lymphoma subtypes.
Keywords: Endocrine Disruptors; Sex Factors; mužské pohlaví; Lymphoma; endokrinní disruptory; Male; pracovní expozice; Humans; Female; nemoci z povolání; lidé; ženské pohlaví; Evropa; rizikové faktory; studie případů a kontrol; Case-Control Studies; sexuální faktory; lymfom; Occupational Exposure; Europe; Occupational Diseases; Risk Factors; incidence; Incidence